WTO Appelate Body in crisis: The way forward - Anwarul Hoda (Indian Council for Research on International Economic Relations (ICRIER), 2021)
The Appellate Body of the WTO has been in abeyance since December 11, 2019. The situation has been brought about by the US veto on filling up vacancies in the Appellate Body on account of its dissatisfaction withits functioning. Although WTO Members have been discussing proposals to set the matter right, they have not been able to agree on the way forward. Thispaper traces the evolution of the dispute settlement in the GATT 1947 and the WTO and analyses the pivotal position that the Appellate Body now occupies in it. It avers that putting the Appellate Body back in position is the most important challenge facing the WTO Members today. The abeyance of the Appellate Body has seriously affected the automatic and binding nature of the dispute settlement system of the WTO that was its hallmark. Binding dispute settlement provides a firmer foundation for arules-based multilateral trading system. When negotiations play a role in disputes,there is greater scope for power play putting the less powerful economies in an unfavourable position. The paper finds merit in the US criticism of the functioning of the Appellate Body and suggests that the way forward is on the basis of the Draft Decision alreadyprepared for the General Council. A possible addition in the Draft could be the proposal for adoption of an authoritative interpretation suggested in the paper.
Keywords: F13; F53; F55; 330; Dispute Settlement; World Trade Organisation